Efektivitas karet alam termoplastik sebagai peningkat indeks viskositas minyak pelumas kendaraan - Puspitasari, Santi; Arifianto, Muhammad Lutfi; Kurniati, Mersi (Majalah Kulit, Karet, dan Plastik, 2016)
Diversification of rubber goods are highly needed to enhance natural rubber domestic consumption. One of the efforts is by using thermoplastic natural rubber that is synthesized from emulsion graft copolymerization of natural rubber latex with thermoplastic monomer as index viscosity improver of lubricating oil. The research aimed to study the effect of thermoplastic natural rubber (natural rubberâstyrene copolymer) addition, at various concentration, into base paraffinic lube oil (HVI 60 and HVI 650) on index viscosity value of lubricating oil. The result showed that emulsion graft copolymerization at composition ratio of natural rubber to styrene monomer 85:15, at 65oC for 7 hours, with addition of 1% ammonium peroxidisulfate as initiator and 2% sodium dodecyl sulfate as surfactant produced thermoplastic natural rubber (TPNR, copoly NR-ST) with grafting efficiency of 56,48%. The TPNR can be functioned properly as index viscosity improver at 5% concentration to base paraffinic lube oil either HVI 60 or HVI 650. The obtaining new lubricating oils could fulfill the index viscosity standard requirement refered to Decree of Directorat General of Oil and Gas No 85K/34/DDJM/1998, and could compete with the commercial lubricating oil type 20W-50, 10W-40, and 15W-40.